IRF3-mediated lncRNA FTX promotes cell proliferation, migration, invasion and suppresses cell apoptosis in oral squamous cell carcinoma by up-regulating FCHSD2 via miR-708-5p: IRF3-mediated lncRNA FTX promotes cell - Zhou, Chun; Fan, Xiaodan; Zhang, Junye (Cellular and Molecular Biology, 2023)
In recent years, researches into the molecular mechanisms of oral squamous cell carcinoma (OSCC) have improved greatly but effective targeted therapies remain elusive. More and more evidence has referred to long non-coding RNAs (lncRNAs) as modulators of carcinomas development. As a novel lncRNA, five prime to Xist (FTX), as reported before, is overexpressed in a variety of cancers. In the present study, we sought to unclose the impacts of FTX and its molecular mechanism in OSCC. Related gene expression levels were disclosed by qRT-PCR and we found that FTX was notably overexpressed in OSCC. The biological functions of FTX in OSCC were measured by functional assays. The results displayed that depletion of FTX hinderedOSCC cell migratory, invasive and proliferative abilities, but promoted cell apoptotic levels. The relationship among interferon regulatory factor 3 (IRF3), FTX, microRNA-708-5p (miR-708-5p) and FCH and double SH3 domains 2 (FCHSD2) was determined by several mechanism assays, from which we discovered that FTX activated by IRF3 regulated FCHSD2 expression by sponging miR-708-5p. Rescue experiments showed that FTX motivated OSCC development by modulating miR-708-5p/FCHSD2 axis. In summary, FTX was an oncogene in OSCC and might provide new insights into OSCC treatment.